2007
DOI: 10.1007/s10291-007-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive wavelet transform based on cross-validation method and its application to GPS multipath mitigation

Abstract: Global positioning system (GPS) multipath disturbance is a bottleneck problem that limits the accuracy of precise GPS positioning applications. A method based on the technique of cross-validation for automatically identifying wavelet signal layers is developed and used for separating noise from signals in data series, and applied to mitigate GPS multipath effects. Experiments with both simulated data series and real GPS observations show that the method is a powerful signal decomposer, which can successfully s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…Some methods [11,12] have been proposed to calculate s k on the premise of a particular noise class. Here we employ a method [13] based on cross-validation [14] to adaptively calculate s k , since this method has no restriction to the noise type. The procedure is as follows.…”
Section: B Filtering Based On Cross-validationmentioning
confidence: 99%
“…Some methods [11,12] have been proposed to calculate s k on the premise of a particular noise class. Here we employ a method [13] based on cross-validation [14] to adaptively calculate s k , since this method has no restriction to the noise type. The procedure is as follows.…”
Section: B Filtering Based On Cross-validationmentioning
confidence: 99%
“…Global Positioning System (GPS) has been successfully applied in the short-or longtime structural health monitoring (SHM) of the long-and short-period domains of large-scale civil engineering structures (Meng 2002;Zhong et al 2008;Im et al 2011). Yu et al (2006) summarized the advantages of GPS to monitor the deformation of civil structures.…”
Section: Introductionmentioning
confidence: 99%
“…Solutions to filtering (Ko & Fox 2009) and smoothing (Godsill et al 2004) in linear dynamic systems are well known, and numerous approximations for non-linear systems have been proposed, for both filtering (Ko & Fox 2009) and smoothing (Godsill et al 2004). Some researchers choose the filtration and smoothed models to mitigate the GPS errors as references (Meng 2002;Yu et al 2006;Psimoulis et al 2008;Zhong et al 2008;Kaloop 2012), and others used multiple antennae to reduce the multipath error and then used filtrations of observation also as references (Meng 2002;Roberts et al 2002;Danskin et al 2009;Oluropo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al [20] found that the period of the multipath effect is proportional to the distance between the antenna and refactor, and this relation is very sensitive to the distance change and appeared to be periodical. Other papers [21,22] also indicated that multipath effect caused by close distance reflection appeared to be in low frequency and periodical and recommended various filtering methods to weaken multipath.…”
Section: Gps Multipath Effect and Its Featuresmentioning
confidence: 99%